TREATMENT OF CHRONIC CONSTIPATION IN CHILDREN - E.A. Korniyenko ("Paediatrician" Publishers LLC, 2010)
Constipation is one of the most frequent complaints and is seen in 3% of children, in 90% it has functional character. The pathogenesis of chronic constipation has 3 mechanisms: decrease of propulsion motor function and visceral sensitivity of rectum and functional disorder of faeces evacuation. Chronic constipation has a trend to the progression due to overstretched rectum and decrease of its sensitivity independently of its specific reason. A treatment of functional constipation must be started from correction of diet and drinking regimen and only if these measures are ineffective, the clearance of bowels and administration of laxatives should be performed. There are only few drugs approved for the use in pediatric practice. They are osmotic laxatives and drugs with combined effect (Guttalax).Key words: children, constipation, pathogenesis, treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(2):136-140)